Reassessing biopsychosocial psychiatry. (January 2017) - Davies, Will; Roache, Rebecca
Summary: Psychiatry uncomfortably spans biological and psychosocial perspectives on mental illness, an idea central to Engel's biopsychosocial paradigm. This paradigm was extremely ambitious, proposing new foundations for clinical practice as well as a non-reductive metaphysics for mental illness. Perhaps given this scope, the approach has failed to engender a clearly identifiable research programme. And yet the view remains influential. We reassess the relevance of the biopsychosocial paradigm for psychiatry, distinguishing a number of ways in which it could be (re)conceived.